Heart-fatty acid binding protein in dogs with degenerative valvular disease and dilated cardiomyopathy. (February 2019) - Lam, C.; Casamian-Sorrosal, D.; Monteith, G.; Fonfara, S.
Highlights: Plasma heart-fatty acid binding protein (HFABP) concentrations were higher in dogs with acquired cardiac disease. Plasma HFABP concentrations were higher in dogs with more severe disease; control dogs had lowest HFABP. A reduction of HFABP over time was observed in more severely affected dogs and dogs with dilated cardiomyopathy. HFABP concentrations at initial presentation was an independent predictor of survival in a univariate analysis. HFABP may be useful as marker for disease severity, treatment and prognosis in dogs with acquired cardiac disease. Abstract: The study objective was to investigate heart-fatty acid binding protein (HFABP) concentrations in dogs with degenerative valvular disease (MVD) and dilated cardiomyopathy (DCM), and its potential as a prognostic factor. Plasma HFABP, N-terminal pro brain natriuretic peptide (NTproBNP) and serum cardiac troponin I (cTnI) levels were measured in 21 control dogs, 23 dogs with MVD and 13 dogs with DCM, with repeated sampling at 1 and 3 months after initial presentation. All dogs were followed up after 6 and 12 months to verify survival. Heart-fatty acid binding protein concentrations were significantly higher in dogs with MVD and DCM than controls at initial presentation, and after 1 month in dogs with MVD. For dogs with DCM, a significant reduction in HFABP levels over time was observed. Comparing ACVIM stages, highest HFABP concentrations were detected in ACVIM stage C dogs compared to stage B, with the lowest levels seen in controls, and a reduction over time in stage C dogs was present. Similarly, cTnI concentrations were higher in DCM and stage C in comparison to control dogs and reduced over time, while NTproBNP concentrations were only higher in diseased dogs at 1 month. Heart-fatty acid binding protein and cTnI levels at initial presentation and ACVIM disease stage were independent predictors of survival in a univariate analysis. The elevation of HFABP in dogs with MVD and DCM in comparison to controls, its association with disease severity, and its potential in predicting reduced survival, suggest that HFABP might be useful as marker for canine MVD and DCM.